Ambivalent occupational identities under modern workplace demands: the case of Swiss retail apprentices - Duemmler, Kerstin [Verfasser]; Felder, Alexandra [Verfasser]; Caprani, Isabelle [Verfasser] (My University, 2018)
"This article investigates how Swiss retail apprentices construct their occupational identities under modern workplace affordances. The Swiss retail sector has become more competitive in recent decades; as a consequence, retail businesses look for skilled and responsible employees who are flexible in regard to work tasks and schedules. The article focuses on apprentices' experiences and sense-making, and specifically examines how retail work conditions not only generate pressure and insecurity, but also offer possibilities for personal identification. Results are based on a qualitative study with retail apprentices involving interviews, focus groups, and observations in vocational education and training schools. Retail apprentices strongly identify with the skilled nature of retail work and even the demand for continuous skill development to ensure that they remain employable. However, they are more critical of the flexible way in which their work is organised and develop divided sense-makings around the demands for responsible autonomy. In short, retail work is perceived in ambivalent ways, oscillating between valorising some of the realities of retail work and suffering from others. The discussion points to the kinds of working and learning conditions within companies that hinder apprentices' ability to cope with the demands of the modern retail workplace." (Authors' abstract; BIBB-Doku)
Keywords: S 6.4.1 Kaufleute; P 2.3 Auszubildende; G 2.3.1 Arbeitsteilung & -organisation; Kaufmännischer Beruf; Kaufmann im Einzelhandel; Auszubildender; Berufliche Identität; Beschäftigungsfähigkeit; Arbeitsbedingungen; Schweiz